On Hyper ρ/δ-Algebra (Baghdad Science Journal, 2023)
In this work, new concepts of algebra structures such as hyper algebra, Hyper algebra were defined. These concepts are introduced by using a hyper operation * on   is a mapping from   to the non-empty power set     i.e.    , ,   and    defined as     and        .  Let     be a hyper structure such that , in hyper structure   a hyper order is a relation was defined by      , with some properties. Also, some examples to illustrate our notions are given. And the relationship between these concepts is also discussed.